Smart home system - YI YAJUN; ZHU HONGJIE; YU LIN; LIN XIBIAO; CHEN CHUNCHENG (2017)
The utility model provides a smart home system, includes host system, network module, sensor module, speech control module, display module, security protection module and user terminal equipment, and host system and network module are connected, and host system and speech control module connect, and host system is connected with the display module, and host system is connected with the security protection module, and host system and sensor module are connected, and the network module is connected with user terminal equipment, host system is connected with a DS1307 clock module. Through pronunciation and user terminal equipment control entire system, the structure security is high, easy operation, and the interaction is good. 种智能家居系统，包括主控模块、网络模块、传感器模块、语音控制模块、显示模块、安防模块和用户终端设备，主控模块和网络模块连接，主控模块和语音控制模块连接，主控模块与显示模块连接，主控模块与安防模块连接，主控模块与传感器模块连接，网络模块与用户终端设备连接；所述主控模块连接有DS1307时钟模块。通过语音和用户终端设备控制整个系统，结构安全性高，操作简单，交互性好。